Forest Damage on Sumbawa Island West Nusa Tenggara in an Ecological Justice Perspective - Yahya, M.; Ridwan, Ridwan; Firmanto, Taufik; Wulandari, Ainun; Gufran, Gufran; Sukirman, Sukirman; Adnan, Adnan; Amin, Muhammad (Journal of Transcendental Law, 2024)
This article is the result of legal research that analyzes forest destruction on Sumbawa Island, West Nusa Tenggara from the perspective of ecological justice, focusing on the concept of ecological justice in forest management on Sumbawa Island, and policies on forest utilization on Sumbawa Island with the corn industry program which actually resulted in a crisis. environment in the form of forest destruction. The purpose of this study was to analyze forest destruction on Sumbawa Island, West Nusa Tenggara Province from the perspective of Ecological Justice, by conducting an analysis of forest management policies on Sumbawa Island. The method used in this study is a normative research method with a conceptual approach, statutory approach, conceptual approach, comparative approach, and analytical approach. The results of this study indicate that there has been massive forest destruction, for this reason the application of the concept of ecological justice in forest management on Sumbawa Island still needs to be implemented massively. This departs from the fact that massive forest destruction (natural exploitation) and/or environmental damage continues to occur, but an effective settlement of environmental cases has not yet been found. Likewise with the forest utilization policy on Sumbawa Island which still really needs a concrete role from the government and also the regional government of NTB . For the sake of realizing ecological justice, it cannot be separated from the role of the government as an institution authorized to implement laws and regulations. As the government as the guardian and/or executor of the law on the protection and management of the environment provides a sense of fairness in managing the environment. Keywords: Ecological Justice; Deforestation; West Nusa Tenggara; Sumbawa Island.